Space‐time variability of the rainfall over the western Mediterranean region: A statistical analysis. Issue 15 (15th August 2013) - Rysman, J.‐F.; Verrier, S.; Lemaître, Y.; Moreau, E.
Abstract : [1] This study aims at better understanding the space‐time statistical properties of rain over a Mediterranean region. To this end we analyzed temporal, spatial, and spatio‐temporal spectra of rain field maps provided by an X‐band radar situated in the southeast part of France. The database extends from 2009 to 2012 and has a spatial and temporal resolution of 1 km 2 and 5 min. The analysis highlights several scaling regimes, which are interpreted in terms of meteorological structures (convective cells, mesoscale structures, and midlatitude cyclones). The analysis of spectra per month confirms the dependency of the spectral signature to the underlying meteorological process. Nevertheless, our results also reveal that for a given range of scales (20–45 min in time and 7–20 km in space), spectral slope is monthly invariant. It means that rain behaves identically, in terms of scaling, whatever the mechanism that generated it (convection, front). Moreover, spectral analysis shows that the temporal decorrelation scale is 10 days, which can possibly be related to the longest lifetime of a meteorological phenomenon in the region (i.e., about 10 days). An approach to compute the scaling anisotropy between space and time is proposed. It reveals that, over two distinct ranges of scales (7–20 km/20–45 min and 20–70 km/45 min–3 h), the scaling anisotropic coefficient is equal to 2. It also reveals that the ratio of spectral slope of 2‐D angle averaged spatial spectrum versus 1‐D temporal spectrum is equal to 1 over these ranges of scales. It suggests a similarity in the second‐order properties (e.g., correlation) of temporal and spatial rain field. All these results are important to better understand rainfall statistical behavior and could also be used for the development of downscaling schemes and the validation of numerical weather models. Key Points: Several scaling regimes are found in spatial and temporal spectra of rainfall Meteorological processes impact the scaling behavior of rainfall Space‐time spectral slope ratio equals 1 over two distinct range of scales